Profile of retinal nerve fibre layer symmetry in a multiethnic Asian population: the Singapore Epidemiology of Eye Diseases study. Issue 6 (26th September 2019) - Tao, Yijin; Tham, Yih Chung; Chee, Miao Li; Majithia, Shivani; Thakur, Sahil; Soh, Zhi-Da; Cheung, Carol Yim-Lui; Sabanayagam, Charumathi; Wong, Tien Yin; Cheng, Ching-Yu
Abstract : Background: To examine the normative profile and determinants of retinal nerve fibre layer (RNFL) symmetry in a non-glaucoma, multiethnic Asian population. Methods: Chinese, Malay and Indian adults aged ≥40 years were recruited from the Singapore Epidemiology of Eye Diseases study. Participants underwent standardised systemic and ocular examinations. RNFL thickness was obtained using a spectral-domain optical coherence tomography (Cirrus HD-OCT). RNFL symmetry (in %) was calculated based on Pearson correlation coefficient between the RNFL thickness profiles of the right and left eyes. Multivariable linear regression analysis was used to investigate the associations between ocular and systemic factors with RNFL symmetry. Results: 4211 participants (1227 Chinese, 1245 Malays, 1739 Indians) were included. The mean RNFL symmetry was 86.7%±8.5% in Chinese, 84.7%±10.2% in Malays and 84.0%±10.7% in Indians. The fifth percentile limit of RNFL symmetry was 71.2% in Chinese, 65.0% in Malays and 62.0% in Indians. In multivariable analysis adjusting for age, gender, ethnicity, hypertension, diabetes, hyperlipidaemia, intereye absolute differences in intraocular pressure (IOP), axial length and disc area, Malays (β=−0.9; p=0.03) and Indians (β=−1.76; p<0.001) were found to have lower RNFL symmetry compared with Chinese. Older age, greater intereye differences in IOP, axial length and disc area were significantly associated with lower RNFL symmetry (all p≤0.003). Conclusions: In non-glaucoma individuals, intereye RNFL profile is less symmetric in Malays and Indians than that in Chinese. This also suggests that current commercial optical coherence tomography's deployment of a single, universal RNFL symmetry cut-off for glaucoma detection is flawed, and ethnic-specific cut-off is warranted.